KONTROL SISTEM PENDINGIN TRANSFORMATOR UTAMA DI PT PLN NUSANTARA POWER UP PLTU INDRAMAYU - ., Apriliana; Latifa, Ulinnuha (Politeknik Harapan Bersama Tegal, 2024)
In an era marked by technological advancement, the demand for electrical power continues to surge, particularly in the midst of globalization and digitalization where electricity has become indispensable in daily life. State-owned electricity provider PLN is tasked with efficiently meeting this demand. To achieve this, PLN has established power generation facilities known as power plants. Electricity transmission from these plants to substations is facilitated through long-distance transmission systems like the SUTET cables. Before reaching substations, voltage from power plants such as PLTU Indramayu is boosted using Main Transformers. Despite meticulous preparation by PLN, challenges persist due to aging infrastructure, necessitating proactive maintenance programs. A critical aspect of infrastructure maintenance is the cooling system for transformers, crucial for voltage regulation. PLN employs the Oil Forced Air Forced (OFAF) mode for cooling the main transformers at PLTU Indramayu, ensuring efficient operation based on oil and winding temperature indicators. This system offers cost-effective maintenance and operation, boasting a capacity of 16 EA motor fans and 6 EA motor pumps, each operating at 380V 3 phase.